2017
DOI: 10.1016/j.jad.2017.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological correlates of suicidal ideation in major depressive disorder: Hyperarousal during sleep

Abstract: Background Suicide is a major public health concern, and a barrier to reducing the suicide rate is the lack of objective predictors of risk. The present study considers whether quantitative sleep electroencephalography (EEG) may be a neurobiological correlate of suicidal ideation. Methods Participants included 84 (45 female, mean age=26.6) adults diagnosed with major depressive disorder (MDD). The item that measures thoughts of death or suicide on the Quick Inventory of Depressive Symptomatology (QIDS) was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 71 publications
2
23
0
1
Order By: Relevance
“…Perhaps the most novel and interesting finding observed here is the mixing of alpha and delta rhythms during sleep, originally reported by Adams et al (15) and identified here as alpha-delta sleep (16). Although the functional role and underlying circuit mechanisms of alpha-delta sleep have remained elusive (59, 60), the phenomenon has been reported in a variety of conditions including fibromyalgia/chronic fatigue (25, 26), rheumatoid arthritis (24), schizophrenia (16), major depressive disorder (29) with implications for suicidality (61), anxiety (28), and in healthy individuals with induced pain and/or arousal during sleep (62). To our knowledge, this is the first report of alpha-delta sleep in the severely injured brain.…”
Section: Discussionmentioning
confidence: 99%
“…Perhaps the most novel and interesting finding observed here is the mixing of alpha and delta rhythms during sleep, originally reported by Adams et al (15) and identified here as alpha-delta sleep (16). Although the functional role and underlying circuit mechanisms of alpha-delta sleep have remained elusive (59, 60), the phenomenon has been reported in a variety of conditions including fibromyalgia/chronic fatigue (25, 26), rheumatoid arthritis (24), schizophrenia (16), major depressive disorder (29) with implications for suicidality (61), anxiety (28), and in healthy individuals with induced pain and/or arousal during sleep (62). To our knowledge, this is the first report of alpha-delta sleep in the severely injured brain.…”
Section: Discussionmentioning
confidence: 99%
“…One hypothesis suggests that tetrahydrocannabinol (THC, the active ingredient of cannabis) has direct neurophysiological effects that lead to impaired cognition and behavior, whereas another hypothesis suggests that cannabis use indirectly increases one’s risk for suicide attempt because cannabis users tend to have other predisposing social factors that increase their risk of attempting suicide [ 9 ]. Having a psychiatric disorder including other substance use is likely associated with altered neurophysiological state and therefore the effect of cannabis is less well known and difficult to isolate from the underlying psychopathology [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Suicidal ideations in adolescents showed an increase in activation in both the dorsal anterior cingulate cortex and dorsal lateral prefrontal cortex; this dysregulation can be due to the dorsal area of the brain being in charge of decision making and the control of emotions and behavior. Dolsen et al., (2017) conducted a study in which it was hypothesized that hyperarousal during sleep correlated with suicidal ideations as well as a major depressive disorder ( Dolsen et al., 2017 ). Neurophysiological hyperarousal occurs when the brain is at a constant state of high alert, which can lead to long-lasting stress.…”
Section: Neuroimaging and Neurophysiology Of Suicidal Behaviormentioning
confidence: 99%
“…Neurophysiological hyperarousal occurs when the brain is at a constant state of high alert, which can lead to long-lasting stress. During sleep, hyper arousal can be reflected by an increased alpha and beta activity, as well as a slow frequency in delta activity ( Dolsen et al., 2017 ). EEG studies on sleeping patterns have shown that neurophysiological hyper arousal during sleep may contribute to suicidal behavior when paired with major depressive disorder ( Dolsen et al., 2017 ).…”
Section: Neuroimaging and Neurophysiology Of Suicidal Behaviormentioning
confidence: 99%